Does Bank Governance Reduce Financial Statement Fraud? The Moderating Role of Operational Risk - Saraswati, Ety; Agustina, Iin (University of Merdeka Malang, 2022)
The complexity generally triggers the opportunity of fraud in operation experienced, so that it can potentially be a serious threat which has a significant loss impact for the company. This study focuses on the indications of financial statement fraud committed by commercial banks in Indonesia. The purpose of this study is to examine whether the implementation of good corporate governance can reduce fraudulent financial statements activity in banks, using the moderating role of operational risk. The population determined is all commercial banks listed on the IDX for 2016 to 2020. All 25 banks that met the specified criteria were used as research samples. The data analysis technique used the Moderated Regression Analysis (MRA) method analyzed with SPSS Software. The research findings reveal no significant relationship between Bank governance and financial statement fraud directly. However, operational risk is shown to have a moderating role in the relationship between Bank governance and financial statement fraud. In addition, operational risk also has a function as a predictor concerning fraud. Overall findings of this study are exciting because the interaction between corporate governance and operational risk can influence the company's decisions on the possibility of fraudulent financial statement activities. The benefits of this research are expected to provide input for bank management in assessing the level of corporate governance implementation and response plans for financial statement fraud actions that have a significant impact on high operational risk costs. In addition, it can provide information for regulators in supervising and evaluating regulations related to anti-fraud strategies set in commercial banks and for investors to ensure the security of their investments to increase investor confidence in banks. Finally, it suggested that further research reconsider the concept and size of the study and add new concepts to provide more determinant factors that affect fraudulent financial statements in companies.